ANALISIS KOMPETENSI KEPRIBADIAN GURU TK SE KECAMATAN TALAMAU KABUPATEN PASAMAN BARAT - Tris Madona; Daviq Chairilsyah; Wusono Indarto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This descriptive study aims to reveal the personality of the teacher competency kindergarten Talamau at Subdistrict of West Pasaman. The sample in this study is a kindergarten teacher Talamau at Subdistrict of West Pasaman many as 49 teachers. The data collection technique using a questionnaire containing statements about the competence of the teacher's personality Early Childhood Education. Analysis data technique using large-scale testing and analysis of statistical methods with SPSS for Windows Ver. 20. Based on the results of this study concluded that personal competence kindergarten teachers throughout the at Subdistrict Talamau West Pasaman as many as 49 teachers earn a percentage 85.22%, in the category "High" is 81-100%. The highest percentage was in the indicator to two that present themselves as a person who is honest, noble and example for young children and people with a percentage of 88.48% based on the value of the assessment categories can be categorized as "High". While the lowest percentage in the four indicators to show the work ethic, high responsibility, self-confidence and pride in being a teacher 82.04% can be categorized as "high", it can be concluded that personal competence of teachers in kindergarten Se-Pasaman of the at Subdistrict Talamau west belongs to the category "High". This is in accordance with the opinion of Syamsul Bahri Talib (2010) personal competence is a personal capacity reflects the personality of a solid, stable, mature, wise and authoritative, become role models for students, and noble.Key words: Teachers, Personality Competence.